Secondary Metabolites in the Arctic Sponge Haliclona viscosa - Spatial and Temporal Variation ... : Sekundärmetaboliten des arktischen Schwamms Haliclona viscosa – räumliche und zeitliche Variation ... - Schmidt, Gesine (Universitätsbibliothek Braunschweig, 2010)
The metabolite screening of Haliclona viscosa yielded 21 3-alkyl pyridinium alkaloids whose structure was unknown before (haliclocyclin C, haliclamine K and J, dehydro-haliclamine J, dehydro-viscosaline E1, viscosamine D, dehydroviscosamine C and D) or had previously been suggested and could be refined or confirmed (haliclocyclin F1, haliclamine E and F, dehydro-haliclamine C, D, F, ambidehydro-haliclamine F and didehydro-haliclamine D, viscosaline B1, B2, E1 and E2, viscosamine B). The structure identification of haliclamines based on a mass spectrometric fragmentation study of the haliclamines; it forms part of this thesis and is enclosed in manuscript form to be published. New viscosalines and viscosamines were identified by evaluation of the high resolution mass spectra of a known viscosaline and viscosamine, and the observations concerning their fragmentation behavior are described in the presented thesis. Structure elucidation of 3-APAs that contain double bonds in the alkyl chains is in progress, as ... : Das Metabolitenscreening in Haliclona viscosa ergab 21 3-Alkylpyridinalkaloide, deren Struktur vormals unbekannt war (Haliclocyclin C, Haliclamine K und J, dehydro-Haliclamin J, dehydro-Viscosalin E1, Viscosamin D, dehydro-Viscosamin C und D), oder deren Struktur suggeriert war und nun weiterenwickelt oder bestätigt werden konnte (Haliclocyclin F1, Haliclamine E und F, dehydro-Haliclamine C, D, F, ambidehydro-Haliclamine F und didehydro-Haliclamine D, Viscosalin B1, B2, E1 und E2, Viscosamin B). Die Strukturaufklärung der Haliclamine basierte auf einer Studie zur massenspektrometrischen Fragmentierung der Haliclamine, die auch Teil dieser Arbeit ist und in einreichbarer Manuskriptform beigelegt wird. Die neuen Viscosaline und Viscosamine wurden durch die genaue Analyse von hochauflösenden Massenspektren eines bekannten Viscosalines und Viscosamines identifiziert. Die neuen Beobachtungen zum Fragmentierungsverhalten dieser Verbindungen sind Teil dieser Arbeit. Die Strukturaufklärung von 3-APAs mit ...